On the Existence and Stability of a Neutral Stochastic Fractional Differential System - Manzoor Ahmad; Akbar Zada; Mehran Ghaderi; Reny George; Shahram Rezapour (Fractal and Fractional, 2022)
The main purpose of this paper is to investigate the existence and Ulam-Hyers stability (U-Hs) of solutions of a nonlinear neutral stochastic fractional differential system. We prove the existence and uniqueness of solutions to the proposed system by using fixed point theorems and the Banach contraction principle. Also, by using fundamental schemes of fractional calculus, we study the (U-Hs) to the solutions of our suggested system. Besides, we study an example, best describing our main result.